The Peer Group as a Context for the Development of Young Adolescent Motivation and Achievement - Ryan, Allison M. (Child Development, 2001)
This study investigated the peer group as a context for the socialization of young adolescents' motivation and achievement in school. Social network analysis was used to identify peer groups of adolescents in middle school whose members regularly interacted with each other (N=331). Actual reports from these peer group members were used to assess peer group characteristics. Multilevel analyses indicated that peer groups did socialize some academic characteristics, controlling for selection factors. Students' peer group context in the fall predicted changes in their liking and enjoyment of school (intrinsic value) and their achievement over the school year. Students' peer group context was unrelated to changes in their beliefs about the importance of school (utility value) or expectancies for success over the school year.